FC026: Chronic High Phosphate Level Impairs Cardiac Health. (3rd May 2022) - Grund, Andrea; Vogt, Isabel; Sophie Richter, Gloria; Richter, Beatrice; Trogisch, Felix; Martin Garrido, Abel; Heineke, Jörg; Dittrich-Breiholz, Oliver; Haffner, Dieter; Leifheit-Nestler, Maren
Abstract: BACKGROUND AND AIMS: Patients with chronic kidney disease (CKD) suffer from disturbed mineral metabolism in which the chronic phosphate load leads to the elevation of the phosphaturic hormones parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23). Persistent hyperphosphatemia predisposes to cardiovascular events and increased morbidity and mortality rates. It is discussed that even in the general population, consumption of highly processed food increases phosphate level, which in turn may increase cardiovascular risk. Here, we aim to elucidate the pathological mechanisms of how chronic high phosphate intake mediates cardiac remodeling and dysfunction, respectively. METHOD: Male C57BL/6 wild type mice received a high phosphate diet containing 2% inorganic phosphate (HPD) or a 0.8% normal phosphate diet (NPD) for 6 months. Echocardiographic analysis and ex-vivo measurements in cardiomyocytes using IonOptix system were assessed to evaluated cardiac function and contractility. Bulk RNA sequencing of whole heart tissue followed by pathway analysis was done to identify affected relevant signaling pathways, which were verified by in vitro studies using neonatal rat ventricular myocytes (NRVM). RESULTS: Chronic phosphate overload resulted in increased level of serum and urinary phosphate and high plasma PTH and FGF23 concentrations. HPD caused impaired heart function as shown by reduced ejection fraction, increased end-systolic volumes and enlarged systolic left ventricular internal diameter accompanied by impaired left ventricular relaxation as seen in Doppler echocardiography. Histological analysis showed increased cardiomyocyte area and length in HPD-fed mice compared with NPD demonstrating cellular hypertrophy. RNA sequencing revealed differentially expressed genes of calcium signaling pathways in the HPD group. Besides, immunoblot analysis of whole heart tissue showed altered Phospholamban activity after 6 months of HPD compared with NPD, indicating altered calcium pump in cardiomyocytes. Preliminary analysis of sarcomere movements and changes of intracellular calcium levels in single cardiomyocytes isolated from NPD and HPD mice after 6 months suggested impaired contractility. Detailed results will be presented here. In vitro stimulation of isolated NRVM with high phosphate induced a hypertrophic growth response, verifying a direct effect of high phosphate on the heart. CONCLUSION: HPD in mice causes a dilated cardiac phenotype including cellular hypertrophy, altered contractility and differentially expressed genes involved in calcium signaling pathways, indicating that a chronic high phosphate load is harmful for the heart also in the general population.